PERBEDAAN PERSEPSI KONSUMEN ATAS FAKTOR PENENTU TEMPAT BELANJA PADA INDOMARET DAN ALFAMART (Studi Kasus Pada Masyarakat Griya Martubung Kelurahan Besar Kecamatan Medan Labuhan) - Elisabeth, - (Jurnal Manajemen dan Bisnis, 2018)
The purpose of this study was to analyze differences in consumer perceptions of the determinants of shopping for products, location, price, convenience of shopping, advertising, and employee services found at Indomaret and Alfamart and to analyze several types of factors that were superior to Indomaret and Alfamart Other retailers are located in Griya Martubung, Kelurahan Besar, Medan Labuhan District. Benefits This research provides information material to Indomaret and Alfamart parties about differences in consumer perceptions of the determinants of shopping places regarding products, location, price, convenience of shopping, advertising, and employee services. For other researchers it can be used as a reference in conducting studies or research with the same subject matter as well as input for parties directly concerned with this research. The number of samples is 200 respondents, the method of collecting data through questionnaires and documentation, the variables studied about consumer perceptions of the determinants of shopping about products, location, price, convenience of shopping, advertising, and employee services owned by Indomaret and Alfamart, methods of data analysis with chi-square. The results showed that there were differences in Indomaret consumer perceptions with Alfamart consumer perceptions on location indicators, the completeness of the products offered, prices and advertisements. The difference mentioned above is that Indomaret is superior compared to Alfamart. While in terms of convenience, shopping and services provided have a significant difference in the sense that Alfamart is superior to Indomaret. Based on the results of testing the hypothesis by Chi-Square (Ï‡2), it is known that there is a significant difference between the perceptions of Indomaret consumers and Alfamart consumer perceptions. This is indicated by the value of itung2 count (Ï‡2 = 61.72)> Ï‡2 table (tabel2 table = 11.07). For the management of Indomaret, it is better to improve policies related to convenience in shopping, such as ease of consumer mobility when shopping and service quality. Meanwhile, Alfamart should evaluate policies related to products, location, price and advertising.